2019
DOI: 10.1002/ajcp.12303
|View full text |Cite
|
Sign up to set email alerts
|

Engaged Against the Machine: Institutional and Cultural Racial Discrimination and Racial Identity as Predictors of Activism Orientation among Black Youth

Abstract: Highlights• We investigate institutional and cultural racial discrimination and Black youth activism orientation.• Racial identity that emphasizes the importance of Blackness relates to low-risk activism orientation.• Nationalist racial ideology promotes high-and low-risk Black community activism orientation.• Relationship between racial discrimination and activism orientation varies by public regard.• Teens and young adults need opportunities to process racism to support low-and high-risk activism.Abstract Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
104
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(127 citation statements)
references
References 41 publications
(54 reference statements)
12
104
2
Order By: Relevance
“…Understanding that inequality exists and forming an ethical commitment to others is central to moral identity development for youth of color (Suad Nasir & Kirshner, 2003), our study underscores the ways in which catalytic political events provide unique opportunities for moral identity development. This finding aligns with other studies regarding the ways in which Black youth experience cultural race-related stress, perceive society’s low regard for Black people, and experience discrimination and how these youth engage in increased activism (Hope, Gugwor, Riddick, & Pender, 2019; Szymanski & Lewis, 2015). Furthermore, internalized racism has been linked to mental health and behavioral problems in children and teens (Priest et al, 2013), while opportunities to understand and act on oppressive forces have been linked to radical healing (Ginwright, 2010).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Understanding that inequality exists and forming an ethical commitment to others is central to moral identity development for youth of color (Suad Nasir & Kirshner, 2003), our study underscores the ways in which catalytic political events provide unique opportunities for moral identity development. This finding aligns with other studies regarding the ways in which Black youth experience cultural race-related stress, perceive society’s low regard for Black people, and experience discrimination and how these youth engage in increased activism (Hope, Gugwor, Riddick, & Pender, 2019; Szymanski & Lewis, 2015). Furthermore, internalized racism has been linked to mental health and behavioral problems in children and teens (Priest et al, 2013), while opportunities to understand and act on oppressive forces have been linked to radical healing (Ginwright, 2010).…”
Section: Discussionsupporting
confidence: 90%
“…YELL seemed to support critical dialogue related to race, electoral politics, and social issues. YELL may be a program that can “promote critical dialogue around racially oppressive sociopolitical systems” (Hope et al, 2019, p. 10). YELL did enable several proven practices that contribute to civic learning, including deliberating over current controversial issues, participating in groups where young people work on projects over time, having the opportunity to exercise their voice and make choices, and discussing the underlying causes of social issues (Gould, Jamieson, Levine, McConnell, & Smith, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Social justice education seeks to recognize oppressive situations, and enables students to acquire the knowledge, skills, and dispositions needed to question and act upon challenges, and to create positive change (Adams & Zuniga, 2018). According to Hope et al (2019), “activism and advocacy for social change are important developmental tasks for adolescents and emerging adults in a democratic society” (p. 1). Corning and Myers (2002) found that individuals with an orientation toward activism were likely to engage in social justice actions in their futures.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Corning and Myers (2002) found that individuals with an orientation toward activism were likely to engage in social justice actions in their futures. In addition, Hope et al (2019) noted “Black youth who perceive that mainstream society does not value Black people (low public regard) may be oriented toward social change efforts that benefit and support the Black community” (p. 3).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…For example, individuals with high private racial regard may express positive feelings (e.g., happiness) about being Black, and some studies suggest that feeling positive about being Black corresponds to better mental health outcomes (Bynum et al, 2008; Sellers et al, 2006). In contrast, public regard concerns how Black individuals perceive the ways in which others—including Black and non-Black people—evaluate Black Americans (Hope et al, 2019). In one study, Black college students who expressed beliefs that others evaluated Black Americans positively tended to be negatively affected by stereotype threat (Ho & Sidanius, 2009).…”
Section: Developmental Significance Of Racial Discrimination and Racimentioning
confidence: 99%